The larynx cancer in vitro study by MRI relaxtion time of water - Domka, Wojciech; Ożóg, Łukasz; Bartusik-Aebisher, Dorota; Aebisher, David (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Squamous cell carcinoma (SCC) of the larynx accounts for a significant percentage of all head and neck cancers. Aim. In this paper we determine the differences in magnetic resonance relaxation time (MRI) of water in cancerous and healthy larynx tissues. Material and methods. This study is aimed on T2 MRI modalities for monitoring morphology of larynx tissue. Results. Our results showed that T2 MRI relaxation time measured in larynx tissue can be used to assess early cancer condition of larynx tissues. The changes of T2 MRI correspond to tumor growth within normal tissue. Conclusion. The study showed potential of MRI for the non-invasive monitoring of larynx condition.
Keywords: larynx tissue; magnetic resonance imaging; T2 mapping; T2 relaxation time